OC-078 Cost Savings and Outpatient Clinic Appointments Saved: A 2 Year Review of a Nurse Led Telephone Advice Line for Inflammatory Bowel Disease. (4th June 2013) - Price, T; Lithgo, K; Johnson, M W
Abstract : Introduction: In 2008 the Luton & Dunstable University Hospital set up a nurse led telephone advice line for inflammatory bowel disease (IBD) patients. This service was set up to provide specialist assistance for GPs, IBD patients and their carers in the community. A recent national audit looking into the role of the IBD specialist nurses highlighted the value patients attribute to easy access specialist advice at the point of need [1]. The patients can call for a range of issues including general advice, their blood results, to change clinic appointments or to discuss patient self management of flares in their IBD. The advice line has become a major component of the IBD nursing post. Objective: To assess the cost savings and number of outpatient appointments (OPAs) saved through nursing intervention using the IBD advice line. Methods: For a 2 year period every phone call to the advice line was logged and recorded. If the advice given help prevent or expedite a patient request for an urgent OPA, then this was recorded. Both the patients' GPs and IBD Consultants were informed of any changes in the patients' clinical management. A cost analysis was made using the national tariff of £85 for a routine OPA clinic visit. Results: In 2011 a total of 1252 phone calls were received. This led to 305 OPAs being saved and 44 being expedited. This saved our local primary care trust (PCT) £25, 925. In 2012 a total of 2205 phone calls were received. This led to 194 OPAs being saved and 58 being expedited. This saved our local PCT £16, 490. Conclusion: There has been a year on year increase in the number of patients using the IBD advice line. In the last 2 years 3457 calls have been received, 499 OPAs have been saved and 102 OPAs have been expedited. Over 2011 and 2012 this nurse led advice line has saved our local PCT £42, 415. As a result of our audit we have managed to secure funding for the advice line where clinical management has been shown to saved a clinic appointment. Disclosure of Interest: None Declared Reference: Mason, I. Holbrook, K. Garrick, V. Johns, K. Kane, M. 2012 Inflammatory Bowel Disease Nursing, results of an audit exploring the roles and activity of nurses with specialist/advanced roles. London. Royal College of Nursing.